Improving the product quality of sea lettuce crips through the implementation of technology processes - I Gusti Ayu Wita Kusumawati; Ida Bagus Agung Yogesawara; Putu Wida Gunawan; Ni Wayan Nursini (University of Merdeka Malang, 2025)
Sea lettuce is commonly consumed fresh in salads. However, its underutilization has attracted the interest of the Giri Sari group of women farmers in Pecatu Village, who are exploring the production of sea lettuce chips. While their families enjoy the chips, they tend to be oily and lack crispness. The group aims to market sea lettuce chips to the community, but faces challenges in achieving and maintaining optimal crispness, durability, and effective packaging. The purpose of this community service is to apply appropriate technology that specifically focuses on the process of draining and packaging products. The methods used include socialisation, technology application, monitoring and evaluation, and ensuring the sustainability of the programme. As a result, there was a 75 percent increase in partners' knowledge and skills regarding the processing of sea lettuce chips. In addition, the quality of the chips improved by 90 percent, and they are now packaged in attractive aluminium foil that extends the product's shelf life by up to three months. With technological support from the PKM team, it is expected that the partners will be able to produce sea lettuce chips that are worthy of being marketed to the community.